Pituitary mammosomatotroph tumor with folliculo-stellate and mucin cells in a child with McCune Albright syndrome - Sadeem Al-Subaie; Mussa H. AlMalki; Maqsood Ahmed; Sadeq Al-Dandan (Elsevier, 2019)
A pituitary tumor is a common manifestation of the endocrinopathies criterion in McCune Albright syndrome. Herein, we report a 12-year-old male with McCune Albright syndrome, who presented with dysmorphic features and tall stature, then, underwent a trans-sphenoidal resection of suprasellar lesion that revealed a pituitary mammosomatotroph tumor with a unique finding of folliculo-stellate and mucin cells. Keywords: McCune Albright syndrome, Pituitary tumor, Mammosomatotroph, Folliculo-stellate cells